DEVELOPMENT OF A CLIMATE CHANGE E-MODULE THROUGH ANALYSIS OF RAINFALL TRENDS AND PATTERNS TO ENHANCE THE 4C SKILLS OF PROSPECTIVE PHYSICS TEACHERS - Widya, Herma; Nurhamidah; Jhoni, Muhammad (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2025)
Climate change education demands innovative strategies that equip future educators with both scientific understanding and 21st-century teaching skills. This study aims to develop and evaluate an inquiry-based e-module on climate change, centered around local rainfall trend data, to enhance the conceptual knowledge and 4C competencies—critical thinking, creativity, collaboration, and communication—of pre-service physics teachers in Indonesia. The research employed the ADDIE instructional design model and involved validation by experts and pilot implementation with 57 student teachers. The e-module was developed using multimedia tools and structured around guided inquiry stages. Validation results indicated high content and media quality, while effectiveness testing showed a significant increase in cognitive learning, with a mean N-Gain score of 0.71. Performance assessments also revealed very high achievements across all 4C dimensions. Participants demonstrated improved analytical reasoning, contextual problem-solving, and scientific communication skills.These findings suggest that integrating local climate data into inquiry-based digital learning modules fosters both cognitive and competency-based outcomes. The module aligns with curricular standards and responds to the growing need for climate-responsive teacher education. It provides a scalable model for future implementation in diverse educational settings and contributes to the advancement of environmental literacy and data-driven pedagogy in science education..